Mislocation vectors for the Tripoli seismic array, Greece, and structural effect implications from backazimuth and slowness residual analysis - Pirli, M.; Pirlis, E.; Voulgaris, N. (Bulletin of the Geological Society of Greece, 2007)
Tripoli Seismic Array, Greece, performance in terms of event location is restricted by its very small aperture and limited number of sensors. Detailed investigation of errors in automatic location results suggests structural and local geology effects. In order to investigate the possibility to correct for systematic errors automatically, mis location vectors were calculated for an extended data-set. Theoretical values were calculated based on earthquake catalogues compiled by the National Observatory of Athens and the ISC. Resulting mis location vectors are characterized by significant vector length, consistent with the large observed backazimuth and slowness residuals, the smaller values being met in the area NE of the array and for epicentral distance values less than 200 km. As expected, resulting corrections mostly concern backazimuth values and are not able to sufficiently affect the final epicentre solution, as the largest automatic algorithm errors are observed in epicentral distance determination. However, the possibility to automatically correct for systematic deviations is verified, and future research with an extended array configuration is expected to provide clearer results, due to significantly lower scatter.